ANALYSIS OF EFFECTIVE SENTENCES IN THE NEWS TEXT OF CLASS XI STUDENTS OF SMK NEGERI 2 LHOKSEUMAWE - Nurmalawati; Widia Tamara; Rifki (RADJA PUBLIKA, 2022)
This study aims to find out the effective sentences in news texts and understand the form or form of effective sentences in the news texts of students in grade XI of SMK Negeri 2 Lhokseumawe. This study focuses on the use of effective sentences in students' news texts which are reviewed from the aspects of parallelism, firmness, frugality, precision, and cohesion. The data in this study is effective sentence errors in the news text of grade XI students of SMK Negeri 2 Lhokseumawe. The source of this research data is the news text of grade XI students of SMK Negeri 2 Lhokseumawe. Based on the results of the research that has been carried out, the use of effective sentences in students' news texts has not led to the effectiveness of sentences, because the requirements to achieve effective sentences have not been met. The analysis of twenty student news texts found many errors, such as three errors in equivalence and unity, three errors in parallelism (pararelialism), four errors in sentence emphasis, and ten errors in frugality.